Quality‐of‐life evaluations in children and adolescents with Ewing sarcoma treated with pencil‐beam‐scanning proton therapy. Issue 12 (2nd September 2022) - Weber, Damien C.; Beer, Jürgen; Kliebsch, Ulrike L.; Teske, Carmen; Baust, Katja; Walser, Marc; Pica, Alessia; Bachtiary, Barbara; Timmermann, Beate; Calaminus, Gabriele
Abstract: Background: With improved survival rates for children with cancer, quality‐of‐life (QoL) issues have increasingly become the focus of attention. We report the QoL of children with Ewing sarcoma (EWS) treated with pencil‐beam‐scanning proton therapy (PT). Methods: A PEDQOL (QoL questionnaire for children 4–18 years) self/proxy questionnaire was used to prospectively assess the QoL of 23 children <18 years with EWS treated with PT. This questionnaire evaluates eight different domains. Children (self‐rating) and parents (proxy‐rating) filled out the questionnaire at the start of PT (E1), 2 months after treatment (E2), and thereafter once yearly (E≥3). Results: Compared with healthy controls, parents rated the QoL of their children at E1 significantly worse in all but two (cognition and social functioning‐ family ) domains. At E4, significant differences between the two groups only remained in three of eight domains. At E1, children self‐rated their QoL significantly worse in the domain Physical functioning ( p = .004) and significantly better in the domain Body image ( p = .044) compared to healthy controls, whereas no significant differences were observed at E4. For the longitudinal comparison E1 versus E4, according to parents, Emotional functioning, Cognition and Social functioning‐ peers were slightly decreased 2 years after PT. The children rated Emotional functioning and Body image poorly 2 years after PT. Conclusions: Children with EWS usually recovered seemingly well to normal QoL levels 2 years after the end of PT. They tended to rate their QoL substantially higher than their parents. However, in the longitudinal analysis at 2 years, children rated their Emotional functioning and Body image scores poorly.